The Urgency of Using El-Saddai and El-Elyon in the Major Prophets - Ragil Kristiawan; Kiedong Kim (Jurnal Ilmiah Tafsir Alkitab, 2025)
The Old Testament prophets had the primary task of returning the people to His Covenant. Throughout their ministry, these prophets often used the name Yahweh as God's covenant name to Israel. Interestingly, the books of the Major Prophets present the fact that the prophets also used the combined names of God El-Saddai and El-Elyon in their writings. What message is being conveyed in the use of these combined names of God? Using the study of Biblical Exegesis, it was concluded that the use of El-Shaddai taught Israel that God is still the greatest Person above all even though His human dwelling place, the Temple, has collapsed. The collapse of this building did not necessarily cause God to collapse as well. The use of El-Elyon in the major prophets provides important news that God is still the highest Person even though His people are being held captive in Babylon. The greatness of the Babylonian king is not comparable to the greatness of God who will later bring Israel out of Babylonian captivity. The use of these two combined names of God provides an important message for the people who are being held captive: God is still the great and high Person and is invincible by anything. For this reason, God's people must still place their trust only in God. The exile they experience is only temporary if they respond with faith. Belief in God must continue to grow when they experience oppression during exile. Keywords: El-Shaddai, El-Elyon, The Major Prophets